MRI-based L1 Vertebral Bone Quality Scores Predict Cage Subsidence Following Transforaminal Lumbar Interbody Fusion Similar to L1 CT Hounsfield Units - Wang, Yongdi; Chen, Qian; Zhu, Ce; Ai, Youwei; Wang, Juehan; Ding, Hong; Luo, Dun; Liu, Limin (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
Cage subsidence is one of the most common complications after transforaminal lumbar interbody fusion (TLIF) and correlates with inferior bone quality. Studies have reported L1 vertebral bone quality score (VBQ) based on MRI to be a promising alternative to evaluating preoperative bone quality. However, to the knowledge of the authors, no study has examined the correlation between L1 VBQ scores and cage subsidence after TLIF.The purpose of the study was (1) to assess the interrelation between the L1 VBQ score and cage subsidence after TLIF; and (2) to compare L1 VBQ and L1 CT Hounsfield Unit (HU) values in predicting cage subsidence after TLIF.We reviewed patients who had undergone TLIF at one institution between 2012 to 2021. Cage subsidence was measured using postoperative lumbar CT based on cage protrusion through the endplates at more than 2 mm. The L1 VBQ score was calculated by dividing mean L1 signal intensity (SI) by mean SI of the cerebrospinal fluid (CSF) at L1. The L1 HU value representing bone mineral density (BMD) was measured using computed tomography. We then performed Student’s t-test for independent samples and logistic regression analyses for statistical analysis. We also conducted receiver operating characteristic (ROC) analysis to assess the predictive ability of the L1 VBQ score and L1 CT HU.Of 233 participants, cage subsidence was observed in 41 patients (17.6%). Comparison between the characteristics of patients between the group with subsidence and the group without subsidence revealed significant differences in the age, VBQ score, and L1 CT HU. Multivariate logistic regression showed that higher L1 VBQ score (OR = 2.499, 95% CI: 1.205–5.180, p = 0.014) and lower L1 CT HU (OR = 0.960, 95% CI: 0.933–0.987, p = 0.005) were associated with an increased rate of cage subsidence. Area under the curve (AUC) analysis of the L1 VBQ score returned 0.735 (95% CI: 0.620–0.850) and the suitable threshold was 3.424 (sensitivity: 82.9%, specificity: 70.7%). The AUC of L1 CT HU was 0.747 (95% CI: 0.642–0.852) and the suitable threshold was 136.5 (sensitivity: 85.4%, specificity: 56.1%).The present study demonstrates that L1 VBQ score and L1 CT HU are reliable predictors with similar performance for cage subsidence after TLIF.
Keywords: lumbar degenerative disease; VBQ score; CT HU; TLIF; cage subsidence